Protective Response Mechanisms to Heat Stress in Interaction with High [CO2] Conditions in Coffea spp. - Martins, Madlles Q. (2018)
This work was supported by national funds from Fundacao para a Ciencia e a Tecnologia through the projects PTDC/AGRPRO/3386/2012, the research units UID/AGR/04129/2013 (LEAF) and UID/GEO/04035/2013 (GeoBioTcc), as well through the grant SFRH/BPD/47563/2008 (AT) co-financed through the POPH program subsidized by the European Social Fund. Brazilian funding from CAPES (grams PDSE: 000427/2014-04, W.P. Rodrigues; 0343/2014-05, MM; 12226/12-2, LM), CNPq and Fapemig (fellowships to FDM, FP, and EC) are also greatly acknowledged.